2017
DOI: 10.1007/s00405-017-4774-6
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation with the nucleus slim modiolar electrode (CI532): a preliminary experience

Abstract: To combine the benefits of perimodiolar stimulation with minimal insertion trauma, a thin, pre-curved electrode (CI532) was recently developed by Cochlear Ltd. (Sidney). This array is held straight prior to insertion by an external polymer reloadable sheath that is removed after full electrode insertion. Sixty-seven patients suffering from severe-to-profound sensorineural hearing loss (mean age 42.2 years; mean duration of the hearing loss 19.6 years; mean PTA thresholds at 250-2000 Hz 92.4 dB HL) were implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 31 publications
2
25
0
2
Order By: Relevance
“…Upon loading of the array, the tip of the silicone sheath may open and spread which aggravates the aforementioned issue. Cuda and Murri [33] reported problems in two out of 61 insertions; in these two cases, several reloads and insertion attempts were required to achieve adequate insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Upon loading of the array, the tip of the silicone sheath may open and spread which aggravates the aforementioned issue. Cuda and Murri [33] reported problems in two out of 61 insertions; in these two cases, several reloads and insertion attempts were required to achieve adequate insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using the Slim Modiolar electrode array showed consistent perimodiolar placement and scala tympani insertions in at least 87% of the patients assessed with imaging [1][2][3]. They reported hearing preservation is better than with older perimodiolar and straight designs, but possibly not as good as hybrid or electroacoustic devices that are specifically designed for hearing preservation [2,3,[9][10][11].…”
Section: Introductionmentioning
confidence: 94%
“…It was observed that independent of the type of electrode used, full scala tympani (ST) position [8] and preservation of residual hearing [8,10] is more likely using a RW or eRW approach, compared to the CS approach. These findings might contribute to the fact that to-date, eRW and RW approaches were used in 91.8% (236/257) of the participants in the five studies that investigated the SPE [11,12,[14][15][16].…”
Section: Rationalementioning
confidence: 99%
“…Characteristics of participants a Participant numbers 1, 2, 4, 5, 6, 9, 10, 13, 18, 20, 22 and 23 were defined as having late onset of hearing loss and participants numbers3,7,8,11,12,14,15,16,17,19 and 21 were defined as…”
mentioning
confidence: 99%